The sickle cell trait affects contact dynamics and endothelial cell activation in Plasmodium falciparum-infected erythrocytes - Lansche, Christine; Dasanna, Anil Kumar; Quadt, Katharina; Fröhlich, Benjamin; Missirlis, Dimitris; Buchholz, Bernd; Sanchez, Cecilia P.; Tanaka, Motomu; Schwarz, Ulrich S.; Lanzer, Michael (Communications biology, 2018)
Christine Lansche, Anil Dasanna et al. investigate the dynamic cytoadhesion behavior of erythrocytes infected with malaria parasite using quantitative flow chamber experiments and computer simulations. They find that parasitized erythrocytes have altered adhesion dynamics, mainly due to differences in cell shape, knob density and membrane bending.